QUALITY OF ETHANOL EXTRACT OINTMENT OF ARECA SEEDS (ARECA CATECHU L.) AS ANTI BACTERIAL STAPHYLOCOCCUS AUREUS QUALITY OF PINANG SEEDS EXTRACT ETHANOL (ARECA CATECHU L.) OINTMENT AS AN ANTI BACTERIAL STAPHYLOCOCCUS AUREUS - Vivi Eulis Diana; Ririyen Dessy Natalia; Anisa Frida Tarigan (Jurnal EduHealth, 2019)
The areca nut plant (Areca catechu L) is a traditional plant that has long been used in traditional medicine for various types of diseases such as a stimulant, stomach disorders, worms, smallpox, cholera, venereal diseases and wounds or skin diseases. One of the factors causing skin infections is the bacteria Staphyloccocus aureus. Areca nut (Areca catechu L.) is a natural ingredient that contains antibacterial compounds, namely phenols, alkaloids, terpenoids, saponins, flavonoids, glycosides and tannins. Objective; to determine the antibacterial activity of an ointment preparation of ethanol extract of areca seeds ((Areca catechu L.) against Staphylococcus aureus. Method; this research used experimental research methods, namely the extract was obtained by maceration method with 96% ethanol, and concentrated using a rotary evaporator. Ethanol extract of seeds areca nut is mixed into the ointment preparation with a concentration of 20%, 30%, and 40%. Results; research shows that the average zone of inhibition in each sample of 20% areca nut extract is 7.86 mm, 30% is 12.23 mm, and 40% is 14.3 mm, positive control is 18.36 mm, negative control is 0 mm. Conclusion; from this research is that the ethanol extract of areca nut seeds can be formulated in ointment preparations with concentrations of 20%, 30%, and 40 % which can inhibit the growth of Staphyloccocus aureus bacteria. The concentration of areca nut ethanol extract which has the strongest antibacterial activity against the growth of Staphyloccocus aureus bacteria is a concentration of 40% with an inhibition zone of 14.3 mm.